Multi-argument distances - Martín, J.; Mayor, G. (Fuzzy sets and systems, 2011)
In this paper, we propose a formal definition of a multi-argument function distance. The conventional definition of a distance is extended to apply to collections of more than two elements. Some general properties of multidistances are investigated and significant examples are exhibited. Finally, we introduce the concept of ball centered at a list in order to extend the one of the usual ball in a metric space.